Effectiveness of The Combination of Psychoeducation and Hand Massage on the Anxiety Levels of New Implant Contraceptive Acceptors - Endang Winarsih; Fauziah Winda Gurnita; Putri Rahma Dini (PT Bukuloka Literasi Bangsa, 2025)
The implant is a hormonal contraceptive device that is inserted under the skin of a woman's upper arm. In 2023, regarding contraceptive method choices in Indonesia, injectable contraceptives dominated with 35.3% of users, followed by oral contraceptives at 13.2%, and contraceptive implants at 10.5%. In Central Java, the use of contraceptive implants reached 617,177 individuals. The use of contraceptive implants is still rare among mothers who are willing to use them and has not yet gained popularity due to certain reasons such as anxiety and fear regarding the implantation process. The pain experienced during implantation can lead to fear and anxiety. To analyze the effectiveness of the combination of psychoeducation and hand massage on the anxiety of new implant acceptors Quantitative research using a quasi-experimental one-group pretest-posttest design. The sample size was 34 new implant contraceptive acceptors. The researcher provided psychoeducation to new acceptors regarding the implant insertion procedure using a leaflet, then administered the intervention, namely hand massage. Psychoeducation was provided in 4 steps for 20 minutes, and hand massage was given for 20 minutes. There was a significant effect on anxiety scores before and after treatment combining psychoeducation therapy and hand massage for new KB implant acceptors with a p-value of 0.000. This study proved effective in reducing anxiety with a p-value of 0.000 < 0.05. It is hoped that future researchers will investigate the relationship between cortisol levels and anxiety. Keywords: MKJP, Hand Massage, Psychoeducation